Influence of community factors on formal care use among older Chinese adults - Zhang, Zihan; Kato, Chieko (Intelektual Pustaka Media Utama, 2025)
Community plays a pivotal role in older adults' well-being and long-term care issues. This study investigates how community factors, including community support and social participation, with self-assessment of health as an intervening variable, influence the use of formal care. Further, how a community contributes to older adults' well-being has also been discussed. Data was collected from older adults (men 150, women 150, age>60 y/o) and was analyzed by using structural equation modeling (SEM). This study used health as an intervening variable to investigate community factors' influence on formal care use. The results find a significant negative influence of social participation and self-assessment of health on the use of formal care. While community support was not found to influence the use of formal care significantly, both community support and social participation could negatively influence the use of formal care by positively influencing the self-assessment of health. Cohabitation has also been found to influence community support significantly positively. In China, where formal care still needs to be more developed, reducing over-reliance on formal care follows Chinese cultural values and economic considerations. Moreover, older people living alone need to be attended to by the community.